Photocatalytic N-Formylation of CO2 with Amines Catalyzed by Diethyltriamine Pentaacetic Acid - Xuexin Yuan; Qiqi Zhou; Yu Chen; Hai-Jian Yang; Qingqing Jiang; Juncheng Hu; Cun-Yue Guo (C)
In the present work, inexpensive and commercially available diethyltriamine pentaacetic acid (DTPA) was used as an initiator to catalyze the N-formylation reaction of CO2 with amines via the construction of C-N bonds in the presence of xanthone as the photosensitizer and PhSiH3 as the reducing agent. After a systematic study of various factors, the optimal conditions for the photocatalytic reaction were obtained: 2.5 mmol of amine, 2.5 mmol of PhSiH3, 10 mol% of DTPA, 20 mol% of xanthone, 1 mL of dimethylsulfoxide (DMSO), atmospheric pressure, and 35 W UV lamp irradiation for 48 h. Under the optimal conditions, the catalyst system afforded high performance for the N-formylation of amines (primary and secondary amines) and CO2, and the yields of the N-formylated products of dialkylamines were above 70%. Further studies exhibit that the catalytic system has a wide scope of substrate applications. For various alicyclic secondary amines, heterocyclic secondary amines, aliphatic primary amines, and aromatic primary amines, the corresponding N-formylation products can be obtained efficiently. In addition, the catalyst can be recycled by simple precipitation and filtration. After five cycles of recycling, there was no significant change in the catalytic and structural properties of DTPA. Finally, a possible reaction mechanism is proposed.